2014
DOI: 10.2131/fts.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Residual metals in carbon nanotubes suppress the proliferation of neural stem cells

Abstract: Carbon nanotubes (CNTs) are used in many fields; however, little is known about the effects of CNTs on the central nervous system (CNS). In this study, we found that extracts of sonicated CNTs suppressed the proliferation of neural stem cells (NSCs). Single-walled CNTs (SWCNTs) and multiple-walled CNTs (MWCNTs) were suspended in PBS (1 mg/mL) and sonicated for 5 hr using a water bath sonicator. Supernatants from both types of CNTs suppressed NSC proliferation. The effects weakened in a dilution-ratio-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Co, Fe, Ni, Mo, etc., are commonly used in the synthesis process of these CNTs and those get entrapped at the edges of the newly synthesized CNTs. These are difficult to remove and still persists in the CNT after harsh treatment of CNTs with inorganic acids [27, 28, 29]. Thus, it becomes difficult to remove these entrapped metals in case of pristine MWCNTs.…”
Section: Discussionmentioning
confidence: 99%
“…Co, Fe, Ni, Mo, etc., are commonly used in the synthesis process of these CNTs and those get entrapped at the edges of the newly synthesized CNTs. These are difficult to remove and still persists in the CNT after harsh treatment of CNTs with inorganic acids [27, 28, 29]. Thus, it becomes difficult to remove these entrapped metals in case of pristine MWCNTs.…”
Section: Discussionmentioning
confidence: 99%
“…CNTs #1, #2, #3, #4, and #5 were suspended in PBS at 1 mg/mL and sonicated in a water-bath sonicator for 30 min as in our previous report (Shigemoto-Mogami et al, 2014b). The visual appearance of these suspensions immediately after the sonication is shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…It has also been reported that nanoparticles themselves induce the generation of ROS and stimulate inflammatory factors in microglia in the absence of phagocytosis (Wang et al, 2011). We and other groups have reported that some CNTs cause cytotoxicity and genotoxicity (Pumera, 2007;Liu et al, 2008;Shigemoto-Mogami et al, 2014b) by ROS production via metal residues that were used as catalysts (Ding et al, 2008;Yazyev and Pasquarello, 2008;Banhart, 2009;Tyagi et al, 2011). The cytotoxicity of the CNT #1 and #2 agglomerates may have been caused via ROS production.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the natural environment, soil and crust are rich in iron, an essential element for plants and microorganisms [ 7 ]. Iron plays a vital role in the process of information transmission and physiological metabolism in cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%